2014
DOI: 10.1007/s00330-014-3153-6
|View full text |Cite
|
Sign up to set email alerts
|

MRI-only lesions: application of diffusion-weighted imaging obviates unnecessary MR-guided breast biopsies

Abstract: DWI measurements are a fast and helpful technique for improved breast lesion diagnosis. DWI application in breast lesions visible only on MRI obviates false-positive, MR-guided biopsies. Flexible ADC thresholds provide rule-in and rule-out criteria for breast lesion malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 33 publications
4
72
0
5
Order By: Relevance
“…Spick et al, applied hierarchized thresholds to suspicious breast lesions only visible on contrast-enhanced MRI [27]. These authors concluded that using a high ADC threshold similar to the proposed Blikely benignB ADC level, 29 of 104 biopsies (34.5 %) could have been omitted.…”
Section: Discussionmentioning
confidence: 95%
“…Spick et al, applied hierarchized thresholds to suspicious breast lesions only visible on contrast-enhanced MRI [27]. These authors concluded that using a high ADC threshold similar to the proposed Blikely benignB ADC level, 29 of 104 biopsies (34.5 %) could have been omitted.…”
Section: Discussionmentioning
confidence: 95%
“…In patients with known breast cancer and clinically suspicious findings, DW imaging has been shown to be of high value in discriminating malignant from benign lesions (8,(16)(17)(18)(19)(20)(21). It has been suggested that DWIBS displays breast lesions even better than DW imaging (9,10), because the background suppression makes breast lesions more conspicuous.…”
Section: Adc Maps and Correlation With Histopathologic Gradesmentioning
confidence: 98%
“…However, this provides mainly morphologic, and, to some extent, functional information . To improve specificity, reduce false‐positive findings, and facilitate an improved response assessment to neoadjuvant treatment, the concept of mpMRI has recently been extended to breast imaging . Multiparametric imaging of the breast aims to simultaneously quantify and visualize multiple functional processes at the cellular and molecular levels to further elucidate the development and progression of breast cancer and the response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there is broad consensus that DWI is a promising imaging biomarker, which provides additional functional information to CE‐MRI. DWI significantly increases the specificity (75–84%) compared to CE‐MRI alone (67–72%), and thus, obviates unnecessary breast interventions without missing cancers . In addition to the differentiation of benign and malignant breast tumors, DWI can potentially be used as a noninvasive biomarker for the differentiation of tumor subtypes, invasive vs. noninvasive disease, tumor receptor status, and tumor grading .…”
Section: Introductionmentioning
confidence: 99%